Religious Diplomacy and Child Marriage: The Role of Transnational Faith Based Institutions - Rafiqi, Fathan; Hastira, Muhammad Fajhriyadi; Maksum, Ali (Prodi Studi Agama-Agama, 2026)
This study examines the role of religious diplomacy in addressing child marriage by analyzing the strategies of three transnational religious institutions: the Holy See, the Organization of Islamic Cooperation, and the World Council of Churches. Using a systematic literature review method, 1,656 articles from the Scopus database were screened and analyzed through content and comparative analysis. The research investigates how these institutions influence the formation of international norms on child protection. Findings show that the Holy See utilizes formal moral diplomacy rooted in conservative family values, the World Council of Churches employs progressive campaigns grounded in gender justice and grassroots networks, while the Organization of Islamic Cooperation remains passive due to internal legal and political fragmentation. Key differentiators in effectiveness include theological flexibility, institutional authority, digital engagement, and commitment to international child rights frameworks. The study concludes that religious institutions can function as norm entrepreneurs shaping global child protection discourse. It highlights the need for inclusive, faith-based advocacy aligned with universal human rights, and recommends further research on collaborative efforts between religious actors and states. These findings contribute to the broader understanding of how religious diplomacy intersects with global justice, especially in contested moral arenas like child marriage